Macroeconomic and bank specific determinants of bank stock return: a case study in Malaysia - Khor, Yong Xin; Lam, Sook Mun; Low, Wai Tung; Yiap, Qian Hua (2022)
This research aims to determine the macroeconomic and bank-specific determinants of the stock return of the banking sector in Malaysia. Eight listed commercial banks are chosen in this research, comprising of Alliance Bank Malaysia Berhad, Affin Bank Berhad, AMMB Holdings Berhad, CIMB Group Holdings Berhad, Hong Leong Bank Berhad, Malayan Banking Berhad, Public Bank Berhad, and RHB Bank Berhad. Secondary data is adopted in this research, and the data are gathered on an annual basis from 2011 to 2020 via the sources of Bloomberg and Bank Negara Malaysia. The dependent variable is bank stock return whereas the independent variables consist of macroeconomic factors, bank-specific determinants, and dummy variable. Macroeconomic variables are interest rate and exchange rate while the bank-specific determinants include bank size, net interest margin, and non-performing loan ratio. This research also takes into account the financial crisis of 2020 by inserting the dummy variable. Preliminary tests and diagnostic checking, for instance, unit root test, multicollinearity, autocorrelation, heteroscedasticity, and normality, have been conducted to verify the reliability of the regression model. Feasible Generalized Least Square (FGLS) regression is the panel data model that has been applied in this research. The results proved that interest rate, exchange rate, non-performing loan ratio, and financial crisis have a significantly negative relationship with bank stock return. On the other hand, bank size and net interest margin show an insignificant relationship with bank stock return. This research is able to provide crucial implications to several parties, which are government, policy makers, bank management, investors, and academicians. Some limitations of this research have been identified, and the corresponding recommendations have been proposed for future researchers to overcome them.